Effect of soil composition in copper (II), lead (II), and zinc (II) ion adsorption capacity - Wei-Hsiang Tan; Noumie Surugau; Awang Bono; Mohd Hardyianto Vai Bahrun; Rubia Idris; Siti Aishah Mohd Ali; Rohana Tair; Sahibin Abd Rahim (Research, Innovation and Creativity Administration Office, 2023)
The ability of soil to bind with heavy metals is related to soil adsorption capacity. Different soil compositions have different adsorption capabilities for heavy metal ions. In this study, the excess adsorption isotherm of binary adsorption by individual heavy metals (Cu2+, Pb2+, and Zn2+) onto different clay–sand ratios was investigated. Five different ratios were examined (1:0, 9:1, 7:3, 1:1, and 0:1). The excess adsorption isotherm was measured using a typical batch adsorption approach, and the experimental data were interpreted using the pseudo-ideal monolayer adsorption model. The adsorption capacities ranged from 0.003 to 1.83 × 10-3 mg/g (Cu2+), 0.007 to 1.62 × 10-2 mg/g (Pb2+), and 2.0 to 1.71 × 10-5 mg/g (Zn2+). The results revealed that increasing the clay composition in the admixture increased the selectivity of Pb2+ more than Cu2+ and Zn2+. The sequence of adsorption capacity in the non-competitive adsorption of different compositions of clay and sand showed the following heavy metal adsorption pattern: Pb2+ > Cu2+ > Zn2+